MENCARI DASAR BERSAMA: TINJAUAN HISTORIOGRAFIS DALAM MENCARI VISI INDONESIA - Andreo Fernandez Rajagukguk (Fakultas Ilmu Budaya universitas Hasanuddin, 2019)
Indonesia is a unique country that has thousands of islands. This unique wants to signify the diversity of ethnic groups and languages in Indonesia. Jean Gelman Taylor in her book, Indonesia. Peoples and Histories (2003), believes that with the diversity of ethnic groups and languages in Indonesia, there are many stories or history of all these ethnic groups that have not even been revealed at all. Of course, this is a